2022
DOI: 10.3389/fimmu.2022.1023255
|View full text |Cite
|
Sign up to set email alerts
|

Non-replicative antibiotic resistance-free DNA vaccine encoding S and N proteins induces full protection in mice against SARS-CoV-2

Abstract: SARS-CoV-2 vaccines currently in use have contributed to controlling the COVID-19 pandemic. Notwithstanding, the high mutation rate, fundamentally in the spike glycoprotein (S), is causing the emergence of new variants. Solely utilizing this antigen is a drawback that may reduce the efficacy of these vaccines. Herein we present a DNA vaccine candidate that contains the genes encoding the S and the nucleocapsid (N) proteins implemented into the non-replicative mammalian expression plasmid vector, pPAL. This pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Along with other viral protein(s), SARS-CoV-2 N-based vaccines confer protection in various animal models against infection by SARS-CoV-2 ancestral virus and variants of concern ( Dangi et al., 2021 ; Jia et al., 2021 ; Jiang et al., 2021 ; Afkhami et al., 2022 ; Castro et al., 2022 ; Wussow et al., 2023 ; Alcolea et al., 2022 ; Deschambault et al., 2022; Ishii et al., 2022 ; Wang et al., 2022 ; Chiuppesi et al., 2022 ; Hajnik et al., 2022 ; Hasanpourghadi et al., 2023 ). However, it remained unclear whether immunization with an N-based COVID-19 vaccine alone could induce immune-mediated control of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with other viral protein(s), SARS-CoV-2 N-based vaccines confer protection in various animal models against infection by SARS-CoV-2 ancestral virus and variants of concern ( Dangi et al., 2021 ; Jia et al., 2021 ; Jiang et al., 2021 ; Afkhami et al., 2022 ; Castro et al., 2022 ; Wussow et al., 2023 ; Alcolea et al., 2022 ; Deschambault et al., 2022; Ishii et al., 2022 ; Wang et al., 2022 ; Chiuppesi et al., 2022 ; Hajnik et al., 2022 ; Hasanpourghadi et al., 2023 ). However, it remained unclear whether immunization with an N-based COVID-19 vaccine alone could induce immune-mediated control of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…1 G) indicate that these SARS-CoV-2 N-specific CD8 + T cells in Ad5‐N vaccination group could not efficiently kill target cells. Based on the protective roles conferred by immunization with SARS-CoV-2 N protein along with other viral proteins ( Dangi et al., 2021 ; Jia et al., 2021 ; Jiang et al., 2021 ; Afkhami et al., 2022 ; Castro et al., 2022 ; Wussow et al., 2023 ; Alcolea et al., 2022 ; Deschambault et al., 2022; Ishii et al., 2022 ; Wang et al., 2022 ; Chiuppesi et al., 2022 ; Hajnik et al., 2022 ; Hasanpourghadi et al., 2023 ), these SARS-CoV-2 N-specific CD8 + T cells might need the collaboration of T cells against other viral proteins to efficiently kill target cells. Without efficient killing, these accumulated CD8 + T cells in Ad5‐N vaccination group might keep expressing IFN‐γ ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeat data may be harder to generate because the FDA has proposed that DNA vaccines prepared using a plasmid DNA previously documented to have an acceptable DNA biodistribution/integration profile could waive biodistribution/persistence studies. Additionally, newer bacterial-plasmid systems without antibiotic resistance genes are under investigation [ 208 ]. One bacterial-free DNA amplification system, the doggybone, has demonstrated an equivalent immune response from an entirely enzymatically constructed linear DNA vaccine [ 209 ].…”
Section: Limitations/concernsmentioning
confidence: 99%
“…DNA vaccines have been used in veterinary and human medicine against pathogens to a limited extent, even though they induce specific protective responses. At present, only a vaccine against hemorrhagic fever in salmonids ( 24 ) and a vaccine against SARS-CoV-2 infection in humans ( 25 ) are available, and preclinical studies with a pPAL-based vaccine have been performed in the mouse model ( 26 ). It has been shown that they induce a robust cellular and humoral immune response.…”
Section: Introductionmentioning
confidence: 99%